Grape/Blueberry Anthocyanins and Their Gut-Derived Metabolites Attenuate LPS/Nigericin-Induced Inflammasome Activation by Inhibiting ASC Speck Formation in THP-1 Monocytes - Behrendt, Inken; Röder, Isabella; Will, Frank; Michel, Gabriela; Friedrich, Elvira; Grote, Daniela; Martin, Zoe; Dötzer, Hanna Pauline; Fasshauer, Mathias; Speckmann, Martin; Kuntz, Sabine; Justus Liebig University Giessen (My University, 2024)
Inflammasomes are multi-protein complexes, which are formed in response to tissue injury, infections, and metabolic stress. However, aberrant inflammasome activation has been linked to several inflammatory diseases. Anthocyanins have been reported to attenuate NLR family pyrin domain-containing 3 (NLRP3) inflammasome activation, but the influence of grape/blueberry anthocyanins and especially their gut-derived metabolites on NLRP3 inflammasome activation in human monocytes remains unclear. Therefore, human leukemic monocytes (THP-1 cells, Tohoku Hospital Pediatrics-1 cells) were preincubated with different concentrations of grape/blueberry anthocyanins, homovanillyl alcohol, or 2,4,6-trihydroxybenzaldehyde (THBA) before the NLRP3 inflammasome was activated by lipopolysaccharide and/or nigericin. Apoptosis-associated speck-like protein containing a CARD (ASC) speck formation, as well as ASC and NLRP3 protein expression, were determined using flow cytometry. Caspase-1 activity was measured in cultured cells, and pro-inflammatory cytokine secretion was determined using enzyme-linked immunosorbent assays. Anthocyanins and their metabolites had no effect on ASC or NLRP3 protein expression. However, THBA significantly inhibited ASC speck formation in primed and unprimed THP-1 monocytes, while caspase-1 activity was significantly declined by grape/blueberry anthocyanins. Furthermore, reduced inflammasome activation resulted in lower pro-inflammatory cytokine secretion. In conclusion, our results show for the first time that grape/blueberry anthocyanins and their gut-derived metabolites exert anti-inflammatory effects by attenuating NLRP3 inflammasome activation in THP-1 monocytes.
Keywords: ddc:640; ddc:360